PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS STEM - Rose Hanny Louvette; Mohammad Budiyanto (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The need for 21st-century skills requires students to have adequate critical thinking skills to face global complexity, but the low analytical capacity of students in science material remains a major obstacle due to the dominance of conventional methods. This quantitative descriptive study aims to analyze the implementation of the Problem Based Learning (PBL) model integrated with the STEM approach in improving critical thinking skills on the topic of fluid pressure. Using a one-group pre-test post-test design, this study involved thirty-one students of grade IX-A of SMP Negeri 4 Surabaya in the 2025/2026 academic year. The research stages include contextual problem identification, science and technology-based collaborative investigations, and evaluation through a ten-item test instrument covering five indicators of critical thinking. The quantitative research findings show a significant increase in learning outcomes with an average initial score of 56.77 jumping drastically to 86.45 in the final score. Data analysis proves that the average N-Gain score reaches 0.7 in the high category, reinforced by the results of the Wilcoxon test with a significance value of p < 0.001. The main conclusion confirms that the integration of the STEM-based PBL model is highly effective in constructing in-depth understanding and training students' independence in formulating solutions to physics phenomena. This cross-disciplinary synergy has been proven to systematically transform passive thinking into critical and adaptive thinking for students' future academic development.